KEABSAHAN NIKAH SIRRI DALAM PERSPEKTIF ULAMA MADZHAB - Moh. Najib Syaf (Al Hikmah: Jurnal Studi Keislaman, 2016)
Marriage according to Islamic law is a contract made by the bridegroom to the bride guardian to submit a dowry to the bride in person. A marriage shall be considered to have the force of law in the face of the legislation, if implemented according to the rules of religion and has been listed by the marriage registrar determined employee legislation.